Revisiting the agreement on agriculture for sustainability : an assessment of the greenbox provisions - Kabre, Rimdolmsom Jonathan (University of Pretoria, 2023)
Mini Dissertation (LLM (International Trade and Investment Law in Africa))--University of Pretoria, 2023.